1997
DOI: 10.1099/00221287-143-2-595
|View full text |Cite
|
Sign up to set email alerts
|

Sequence analysis of pqq genes required for biosynthesis of pyrroloquinoline quinone in Methylobacterium extorquens AM1 and the purification of a biosynthetic intermediate

Abstract: Methylobacterium extorquens AM1 produces pyrroloquinoline quinone (PQQ), the prosthetic group of methanol dehydrogenase. Two gene clusters have been shown to be required for PQQ biosynthesis in this micro-organism and complementation analysis has identified seven pqq genes, pqqDGCBA and pqqEF. The DNA sequence of pqqDGC' was reported previously. This paper reports the sequence of the genomic region corresponding to pqqC'BA. For consistency, the nomenclature of pqq genes in Klebsiella pneumoniae will be followe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
59
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 24 publications
0
59
0
Order By: Relevance
“…PqqD has been shown, through gene knock-out and bioinformatic studies, to be an essential component for PQQ biosynthesis (8,14,15). The crystal structure for XcPqqD indicates that PqqD is a dimer and may form a scaffold for a larger macromolecular complex (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PqqD has been shown, through gene knock-out and bioinformatic studies, to be an essential component for PQQ biosynthesis (8,14,15). The crystal structure for XcPqqD indicates that PqqD is a dimer and may form a scaffold for a larger macromolecular complex (15).…”
Section: Discussionmentioning
confidence: 99%
“…Certain ribosomally derived products rely on radical S-adenosylmethionine enzymes (herein referred to as RS proteins) to catalyze the formation of ␣-carbon thioether bonds or carbon-carbon bonds (8,9). In the subtilosin and the pyrroloquinoline quinone (PQQ) 2 pathways, the RS protein also contains a C-terminal extension referred to as a SPASM domain (subtilosin, PQQ, anaerobic sulfatase maturating enzyme, and mycofactocin).…”
mentioning
confidence: 99%
“…PqqC from K. pneumoniae (NCBI accession no. X58778) was expressed in E. coli and purified as described elsewhere (19).Single-Turnover Kinetics, Peroxide Formation, and Oxygen Uptake.The substrate for PqqC was purified from a pqqC knock-out mutant of M. extorquens AM1 as described elsewhere (17,18). All experiments were performed in 0.1 M potassium phosphate buffer (pH 8.0) at 20°C, and all data fitting was done by using KALEIDAGRAPH (Synergy Software, Reading, PA).…”
mentioning
confidence: 99%
“…It has been shown that the PqqC reaction is accelerated in the presence of molecular oxygen (17) and that it requires NADPH and an uncharacterized activating factor (16) for sustained catalytic activity. Most recently, we elucidated the structure of the PqqC substrate, allowing the overall reaction catalyzed by PqqC to be inferred (18).…”
mentioning
confidence: 99%
“…The gene mxaD encodes the 17 kDa periplasmic protein that directly or indirectly stimulates the interaction between methanol dehydrogenase and cytochrome c L (Toyama et al, 2003), and the other genes in this region are involved in either assembly or regulatory functions (Anthony, 2000;Lidstrom & Tsygankov, 1991). Two other regulatory genes (mxbDM) (Springer et al, 1997) and genes required for synthesis of the PQQ prosthetic group, pqqABC/DE (Morris et al, 1994;Toyama et al, 1997), are found at the mxb locus. The other two known pqq genes (pqqFG) reside within another cluster in the genome (Springer et al, 1996).…”
Section: Introductionmentioning
confidence: 99%